Kopfkino: Phases of quarantine among asymptomatic SARS-COV-2 carriers in Germany - Ferdinand Uellner; Freda Röhr; Claudia Denkinger; Till Bärnighausen; Andreas Deckert; Aurelia Souares; Shannon A. McMahon (Elsevier, 2022)
Although a majority of SARS-COV-2 diagnosis are asymptomatic, presymptimatic or minimally symptomatic, little has been described and understood about the illness careers of these individuals. This study explored the lived experience of a SARS-COV-2 diagnosis and subsequent quarantine among individuals in Germany who were diagnosed with SARS-COV-2 during the second wave of the pandemic (late 2020-early 2021), but whose diagnosis was unexpected due to a lack of a known contact, or the asymptomatic nature of their case at the time of diagnosis. In-depth interviews (n ​= ​22) were conducted by phone or video call, audio-recorded, and transcribed verbatim. Routine debriefings guided data collection and facilitated analysis, which followed a framework approach. Regardless of age, gender or socioeconomic status, data consistently demonstrated a diagnosis and quarantine career marked by five emotional phases: overconfidence, shock and denial, coming to grips and asking questions, enduring, and cautious optimism as quarantine ended. These experiences suggest that providing trustworthy, easily accessible information regarding certain key aspects of the post diagnosis and quarantine period could benefit patients in terms of reducing stress, understanding the consequences of a diagnosis and mitigating foreseeable challenges in terms of personal, logistical and emotional issues. Follow-up research with providers and public health bureaus could inform how to best tailor such messaging for clients who experience an unexpected diagnosis.